Optimism Shapes Mindset: Understanding the Association of Optimism and Pessimism - Dardick, William R.; Tuckwillber, Elizabeth D. (Journal of Interdisciplinary Studies in Education, 2019)
The present study investigated our hypothesis of an underlying relationship between optimism/pessimism and implicit theories of intelligence. We investigated the psychometric properties of optimism and mindset scales in our sample, compared confirmatory factor analysis models of the scales, examined the full measurement model to confirm quality measurement of the final structural phase of investigation, and finally conducted two competing structural equation models. We found that the direct pathway from optimism to growth mindset was significant, and the pathway from pessimism to fixed mindset was also significant. However, there were no significant direct effects of optimism on fixed mindset or pessimism on growth mindset. Measurement, research, and practice implications are discussed.